###### Advertisements

###### Advertisements

**Simplify the expression.**

(38 − 8) × 2 ÷ 5 + 13

###### Advertisements

#### Solution

(38 − 8) × 2 ÷ 5 + 13

= 30 × 2 ÷ 5 + 13

= 60 ÷ 5 + 13

= 12 + 13

= 25

#### APPEARS IN

#### RELATED QUESTIONS

**Simplify the expression.**

50 × 5 ÷ 2 + 24

**Simplify the expression.**

(13 × 4) ÷ 2 – 26

**Simplify the expression.**

140 ÷ [( – 11) × ( – 3) – ( – 42) ÷ 14 – 1]

**Simplify the expression.**

{(220 – 140) + [10 × 9 + ( – 2 × 5)]} – 100

**Simplify the expression.**

`3/5 + 3/8 div 6/4`

**Simplify the expression.**

45 ÷ 5 + 20 × 4 − 12

**Simplify the expression.**

`5/3 + 4/7 div 32/21`

**Simplify the expression.**

3 × {4 [85 + 5 − (15 ÷ 3)] + 2}

**Simplify:**

**Simplify:**

Simplify:

**Simplify:**

8 + 4 ÷ 2 × 5 = ?

1001 ÷ 11 of 13 =?

`27 - [18 - {16 - (5 -overline(4-1))}] = ? `

\[32 - [48 \div {36 - (27 - \overline{{16 - 9}})}] = ?\]

**Simplify:**

Solve: 2 × {25 × [(113 - 9) + (4 ÷ 2 × 13)]}

45 ÷ (7 + 8) – 2 = _________

3 + 9 × 8 = 96

7 × 20 – 4 = 136

40 + (56 – 6) ÷ 2 = 45

Simplify the following numerical expression:

(10 + 17) ÷ 3

Simplify the following numerical expression:

12 – [3 – {6 – (5 – 1)}]

Simplify the following numerical expression:

100 + 8 ÷ 2 + {(3 × 2) − 6 ÷ 2}

The value of 3 + 5 – 7 × 1 is __________

The value of 24 ÷ {8 – (3 × 2)} is ___________

Use BIDMAS and put the correct operator in the box

2 `square` 6 – 12 ÷ (4 + 2) = 10